Istikhdām Istirātījiyyah Al-Af’āl al-Kalāmiyyah al-Injāziyyah f ‘Anāwīn al-Akhbār al-siyāsiyah wa al-Iqtisādiyyah fī qonāti al-Yutub Bī bī sī Niyuz ‘Arabi - Malik Fahad (Taqdir, 2022)
The use of pragmatic strategies in the world of journalism is very influential on the creation of interesting language such as headlines. The pragmatic strategy that is often used in headlines is illocutionary, especially in political and economic news headlines, for this reason the author wants to discuss the illocutionary speech act strategy in terms of its types and functions in news headlines on the “BBC News Arabic YouTube channel” on March 29 – April 2022. This research includes qualitative descriptive research. The method of data collection in this research used the observation and written documents. The results of this research are (1) the types of illocutionary speech acts in political news headlines and economics on the YouTube channel "BBC" News Arabic on March 29 - April 1 2022 namely direct illocutionary speech acts and indirect illocutionary speech acts.(2) Direct illocutionary speech acts in political news headlines and economics on the YouTube channel "BBC" News Arabic on March 29 - April 1 2022 It has functions, among others, assertif to explain and inform, while the indirect illocutionary act functions in it are expressive to criticize, expressive to wonder, expressive to be concerned and directives to warn.